A comparative study between the use of coil spring and power chain on tooth retraction - a clinical and histologic study - Elamparo, Josephine VC.
This paper concentrates on the comparative study of the 2 commonly used sliding mechanics in tooth retraction. These 2 techniques are, the use of power chain and the use of coil spring. Eight healthy dogs of the same age were used in this study, one dog was used as a control and the other 7 were used as the experimental subjects. Histologic and rate of tooth movement comparisons were made between the 2 techniques. The treatment duration was for 4 months with activation done at 3 weeks intervals. Prior to every activation, measurement was done to determine the amount of movement of each tooth being retracted. After the 7 activation, all 8 dogs were sacrificed and histologic evaluation was done. Histologic findings showed that the same tissue response was experience in both techniques. The difference lies in the severity of the condition where coil spring exhibited a less severe type of tissue reaction than that of power chain, except of the gingival reaction where power chain exhibited a better tissue reponse. As to the rate of movement, coil spring created a faster rate of tooth movement than that of the power chain.
Thesis (Master of Science in Dentistry)--University of the Philippines Manila.
Keywords: Orthodontic appliances; Orthodontics, Corrective; Tooth retraction